Protection Analysis Of Third Parties Of Principles Droit De Suite In Execution Of Rights Liability - Serly Nurnaningsih; Amin Purnawan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
This study discusses the protection of third parties from the principle of droit de suite in the execution of Mortgage Rights, problems faced in the protection of third parties from the principle of droit de suite in the execution of Mortgage Rights and the solution.Protection of third parties from the principle of droit de suite in the execution of Underwriting Rights, among others, registration of Underwriting Rights to fulfill the principle of publication, announcement of auction sales in execution of Underwriting Rights and prohibition of auction of third party property. The problems faced in the protection of third parties from the principle of droit de suite in the execution of Mortgage Rights, namely protection of third parties is not direct protection because third parties are not parties to the Underwriting Rights Agreement or do not have a direct legal relationship with the Mortgage Agreement To overcome this, it can be done by involving third parties related to the Underwriting Right object in the Underwriting Agreement.Keywords: Protection; Execution; Mortgage Rights; Third Party.